Determination of the Parameters of Improved Coulter for Introducing Mineral and Organic-And-Mineral Fertilizers - A. Kh. Khadzhiev; S. U. Temirov; O. K. Yuldashev; B. R. Kuramboev (Сельскохозяйственные машины и технологии)
When using the conventional coulters for applying organic-and-mineral fertilizers, reliable technological process cannot be ensured unless a fertilizer funnel is adapted to such fertilizers. (Research purpose) Determination of the parameters of an improved coulter for introducing organic-and-mineral fertilizers. (Materials and methods) The authors conducted theoretical studies using the methods of theoretical and agricultural mechanics, as well as analytic geometry. They also considered the horizontal flow of soil particles under the action of the pointed part of a leg and made diagrams of the progressive speed of a cultivator depending on the cutting-point angle of the coulter leg at friction angles of 25, 30, and 35 degrees. (Results and discussion) An analytical relationship was obtained to determine progressive flowability of organic-and-mineral fertilizers through a coulter funnel. The author also found the cutting-point angle of a coulter leg for introducing fertilizers at a certain depth. In this case they neither stick to the coulter surface nor pack up before entering it. The optimum diameter of the fertilizer funnel was determined as well. (Conclusions) It has been proved that the cutting-point angle of a working tool leg for introducing mineral and organic-and-mineral fertilizers developed according to the research should range from 54 to 66 degrees. The authors have determined that an easy flow of fertilizers can be ensured if the diameter of a fertilizer funnel of a coulter should be not less than 43 millimeters.